Legal Responsibility of the Village Head in Village Asset Management: A Constitutional Study on the Implementation of the Village Law - Re Hatmapradipta Anbiyaa; Amalia Diamantina (Law and Justice research journal, 2026)
Village assets constitute vital economic resources for village autonomy and community welfare. However, legal responsibilities of Village Heads in managing these assets often encounter obstacles, ranging from lack of administrative compliance to misuse of authority. This study aims to analyze the construction of legal responsibility of Village Heads in managing village assets according to Law No. 6 of 2014 concerning Villages and its implementing regulations, and to examine the implementation of these responsibilities in practice along with constitutional implications. The research employs a doctrinal legal approach with conceptual orientation, placing legal doctrines and expert opinions as primary materials and legislation as secondary materials. The analysis uses four theoretical frameworks: Decentralization Theory, Authority Theory, Legal Responsibility Theory, and Constitutional Theory. The findings indicate that Village Heads possess attributive authority as holders of village asset management power, but this authority is accompanied by strict legal responsibilities, both administratively and civilly-criminally. Implementation faces challenges including regulatory comprehension gaps, weak supervision, and lack of public participation. Constitutional analysis reveals that irresponsible management contradicts the mandate of Article 18 of the 1945 Constitution and the welfare goals in the Preamble. Strengthening supervision mechanisms, increasing human resource capacity, and enhancing public participation are necessary to ensure village asset management aligns with constitutional principles.